2020
DOI: 10.1097/tp.0000000000003013
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP8 Deficiency Exacerbates Acute Graft Versus Host Disease in a Murine Model of Allogeneic Hematopoietic Cell Transplantation

Abstract: Background. Gastrointestinal acute graft-versus-host disease (GVHD) occurring after allogeneic hematopoietic cell transplant is an allo-reactive T cell and inflammatory cytokine driven organ injury with epithelial apoptosis as 1 of its hallmark findings and is associated with significant mortality. Tumor necrosis factor (TNF)-alpha-induced protein 8 (TNFAIP8 or TIPE) acts as a negative mediator of apoptosis via inhibition of caspase-3 activation, promotes cell proliferation and Tipe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…TNFAIP8 deficiency induced the downregulation of Ki-67 in non-haematopoietic and haematopoietic cells, increased epithelial cell apoptosis, destroyed the epithelial barrier integrity and increased symbiotic bacterial transmission, resulting in enhanced leukocyte infiltration and inflammatory responses, increased levels of proinflammatory cytokines such as IL-17A, TNF and interferon γ, and increased expression of chemokine (C-X-C motif) ligand 1, which contributes to exacerbating GVHD. This finding suggests that TNFAIP8 plays an important role in maintaining intestinal homeostasis and preventing complications associated with allograft transplantation (80). Controlled overexpression of TNFAIP8 might be an innovative therapeutic for GVHD progression.…”
Section: Regulatory Effects Of Tnfaip8 In Other Conditionsmentioning
confidence: 84%
See 1 more Smart Citation
“…TNFAIP8 deficiency induced the downregulation of Ki-67 in non-haematopoietic and haematopoietic cells, increased epithelial cell apoptosis, destroyed the epithelial barrier integrity and increased symbiotic bacterial transmission, resulting in enhanced leukocyte infiltration and inflammatory responses, increased levels of proinflammatory cytokines such as IL-17A, TNF and interferon γ, and increased expression of chemokine (C-X-C motif) ligand 1, which contributes to exacerbating GVHD. This finding suggests that TNFAIP8 plays an important role in maintaining intestinal homeostasis and preventing complications associated with allograft transplantation (80). Controlled overexpression of TNFAIP8 might be an innovative therapeutic for GVHD progression.…”
Section: Regulatory Effects Of Tnfaip8 In Other Conditionsmentioning
confidence: 84%
“…Allogeneic stem cell transplantation (aSCT) causes chronic graft-versus-host disease (cGVHD), and TNFAIP8 is a candidate molecular target of cGVHD and aSCT (79). In a previous study, allogeneic haematopoietic cell transplantation caused acute GVHD in the gastrointestinal tract, and TNFAIP8-knockout mice exhibited significantly exacerbated GVHD, weight loss and increased mortality rates (80). TNFAIP8 deficiency induced the downregulation of Ki-67 in non-haematopoietic and haematopoietic cells, increased epithelial cell apoptosis, destroyed the epithelial barrier integrity and increased symbiotic bacterial transmission, resulting in enhanced leukocyte infiltration and inflammatory responses, increased levels of proinflammatory cytokines such as IL-17A, TNF and interferon γ, and increased expression of chemokine (C-X-C motif) ligand 1, which contributes to exacerbating GVHD.…”
Section: Regulatory Effects Of Tnfaip8 In Other Conditionsmentioning
confidence: 99%
“…Recently, the role of TNFAIP8 in acute Graft Versus-Host Disease was investigated in a murine model, and the study revealed that TNFAIP8 deficiency in allogeneic C57BL/6 recipient mice have a lower survival rate compared with allogeneic wild type recipients. TNFAIP8 deficiency increased splenic CD4 + cells levels, serum cytokines (IL-17A, TNF, and IL-6) levels, and active caspase-3 expression in the small intestine, whereas, cell survival factor Ki-67 expression was significantly decreased in epithelial cells of small intestine suggesting that TNFAIP8 might be involved in increased GI tract pathology risk [48]. Moreover, the expression of TNFAIP8 and TIPE2 is associated with diabetic nephropathy in glomeruli from streptozotocin (STZ)-induced diabetic rats, and renal biopsies of diabetic patients in vivo [49].…”
Section: The Role Of Tnfaip8 In Inflammation Infection Immunity and Related Human Diseasesmentioning
confidence: 94%